Molecular Mechanisms and Therapeutic Strategies of Chronic Renal Injury: The Role of Nuclear Factor κB Activation in the Development of Renal Fibrosis - Satoshi Tamada; Toshihiro Asai; Nobuyuki Kuwabara; Tomoaki Iwai; Junji Uchida; Kae Teramoto; Noriko Kaneda; Tokihito Yukimura; Toshiyuki Komiya; Tatsuya Nakatani; Katsuyuki Miura (Elsevier, 2006)
Abstract.: Tubulointerstitial fibrosis is a common feature of many progressive renal diseases and is a main determinant that leads to an irreversible loss of renal function. In chronic cyclosporin A nephrotoxicity, we previously reported that inflammatory responses such as macrophage infiltration preceded interstitial fibrosis. This inflammation was accompanied by an elevation in renal nuclear factor κB (NF-κB) activity. Similar findings were obtained in chronic tacrolimus nephrotoxicity and obstructive nephropathy. Inhibition of NF-κB markedly attenuated renal inflammation and interstitial fibrosis in these models. Furthermore, administration of oral adsorbent (Kremezin®) significantly attenuated the increase in renal NF-κB activity and concomitantly reduced interstitial inflammation and renal fibrosis in chronic renal failure rats. Elimination of indoxyl sulfate by this adsorbent is likely involved in this mechanism since it is known that indoxyl sulfate activates NF-κB in renal tubular cells. It is suggested that strategy aiming at NF-κB inhibition is important to prevent the progression of renal fibrosis. Keywords:: nuclear factor κB, renal fibrosis, nephrotoxicity, unilateral ureteral obstruction, oral adsorbent